Initial Management of Epilepsy - Yadav, Bharat Kumar; Sharma, L (Journal of General Practice and Emergency Medicine of Nepal, 2010)
There is no sufficient evidence to prove one anti epileptic drug to be superior to another, so selection of antiepileptic drugs should be individualized according to the patient. Monotherapy should be the goal when anti epileptic drug treatment is instituted for epilepsy.